Topology for Substrate Routing in Semiconductor Package Design. (August 2022) - Seong, Rak-Kyeong; Yang, Jaeho; Han, Sang-Hoon
Abstract: In this work, we propose a new signal routing method for solving routing problems that occur in the design process of semiconductor package substrates. Our work uses a topological transformation of the layers of the package substrate in order to simplify the routing problem into a problem of connecting points on a circle with non-intersecting straight line segments. The circle, which we call the Circular Frame, is a polygonal schema, which is originally used in topology to study the topological structure of 2-manifolds. We show through experiments that our new routing method based on the Circular Frame competes with certain grid-based routing algorithms. Highlights: The proposed geometric transformation simplifies substrate routing problems in semiconductor package design. The proposed geometric transformation maps a substrate layer to a topologically equivalent representation of the original environment. The new environment guarantees full connection during the routing process without the need of rip-out and reroute mechanisms. The proposed topological router is faster and more reliable than standard grid-based routers used for substrate design.